2017
DOI: 10.1104/pp.17.00649
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxyisobutyrate Dehydrogenase Is Involved in Both, Valine and Isoleucine Degradation in Arabidopsis thaliana

Abstract: In plants, amino acid catabolism is especially relevant in metabolic stress situations (e.g. limited carbohydrate availability during extended darkness). Under these conditions, amino acids are used as alternative substrates for respiration. Complete oxidation of the branched-chain amino acids (BCAAs) leucine, isoleucine (Ile), and valine (Val) in the mitochondria efficiently allows the formation of ATP by oxidative phosphorylation. However, the metabolic pathways for BCAA breakdown are largely unknown so far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
(45 reference statements)
2
24
0
1
Order By: Relevance
“…We found that the amino acid metabolism ability of S. pogona overall was stronger than that of S. spinosa, indicating that S. pogona demonstrated a stronger synthetic ability to convert amino acids into acetyl-CoA and other key precursors compared with S. spinosa. For example, the abundance of enzymes (ilvE, bkdA, acdA-3, fadB, fadA, fadA4, pccB, and aldA) involved in the leucine to acetyl-CoA, valine to (R)-methylmalonyl-CoA, and isoleucine to (S)methylmalonyl-CoA pathways in S. pogona was remarkably higher than that in S. spinosa (Schertl et al, 2017). Meanwhile, leucine (0.36) and isoleucine (0.71) were detected at lower concentrations in S. pogona than in S. spinosa.…”
Section: Amino Acid Metabolismmentioning
confidence: 96%
“…We found that the amino acid metabolism ability of S. pogona overall was stronger than that of S. spinosa, indicating that S. pogona demonstrated a stronger synthetic ability to convert amino acids into acetyl-CoA and other key precursors compared with S. spinosa. For example, the abundance of enzymes (ilvE, bkdA, acdA-3, fadB, fadA, fadA4, pccB, and aldA) involved in the leucine to acetyl-CoA, valine to (R)-methylmalonyl-CoA, and isoleucine to (S)methylmalonyl-CoA pathways in S. pogona was remarkably higher than that in S. spinosa (Schertl et al, 2017). Meanwhile, leucine (0.36) and isoleucine (0.71) were detected at lower concentrations in S. pogona than in S. spinosa.…”
Section: Amino Acid Metabolismmentioning
confidence: 96%
“…3-hydroxyisobutyrate dehydrogenase is essential for valine metabolism, and catalyzes a reversible oxidation of L-3-hydroxyisobutyrate to methylmalonate semialdehyde [26]. Leucine and valine concentrations increase under various stress conditions and their complete oxidation allows the generation of high amounts of ATP [27,28]. Furthermore, the protein expression profile showed that other differentially expressed proteins involved in amino acid metabolism were downregulated.…”
Section: Amino Acid Metabolism and Biosynthesismentioning
confidence: 99%
“…It is also involved in degradation of branched-chain amino acids. Knockdown of this gene have reduced degradation of valine and isoleucine the root growth under presence of valine and isoleucine [60]. It seems apparent that these subgenomic biases are instrumental in shaping phenotypes and future plasticity of E. coracana no matter the driving mechanism.…”
Section: Discussionmentioning
confidence: 99%